Muscle-specific expression of hypoxia-inducible factor in human skeletal muscle - Mounier, R.; Pedersen, B. K.; Plomgaard, P. (Experimental Physiology, 2010)
Skeletal muscle is well known to exhibit a high degree of plasticity depending on environmental changes, such as various oxygen concentrations. Studies of the oxygen-sensitive subunit a of hypoxia-inducible factor-1 (HIF-1) are difficult owing to the large variety of functionally diverse muscle fibres that possess unique patterns of protein and gene expression, producing different capillarization and energy metabolism systems. In this work, we analysed HIF-1a mRNA and protein expression related to the fibre-type composition in untrained human skeletal muscle by obtaining muscle biopsies from triceps brachii (characterized by a high proportion of type II fibres), from soleus (characterized by a high proportion of type I fibres) and from vastus lateralis (characterized by an equal proportion of type I and II fibres). The hypothesis was that type I muscle fibres would have lower HIF-1a mRNA and protein owing to their higher oxidative capacity. We have shown, in normoxic conditions, a higher HIF-1a protein expression in predominantly oxidative muscles than in predominantly glycolytic muscles. However, the HIF-1a mRNA expression pattern was not in agreement with the HIF-1a protein level. Interestingly, none of the HIF-1a target genes, like the most studied angiogenic factor involved in muscle angiogenesis, vascular endothelial growth factor (VEGF), exhibited a muscle fibre-specific-related mRNA expression at rest in normoxia. However, soleus presented a significantly higher VEGF protein content than vastus lateralis and triceps muscle. In conclusion, we have shown that there are muscle-specific differences in HIF-1a and VEGF expression within human skeletal muscle at rest in normoxic conditions. Recent results, when combined with the findings described here, support a key role for HIF-1a for maintaining muscle homeostasis in non-hypoxic conditions.